2023
DOI: 10.1096/fj.202201733rrr
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA SNHG11 regulates the Wnt/β‐catenin signaling pathway through rho/ROCK in trabecular meshwork cells

Abstract: Trabecular meshwork (TM) cell dysfunction is the leading cause of elevated intraocular pressure (IOP) and glaucoma. The long non-coding RNA (lncRNA) small nucleolar RNA host gene 11 (SNHG11) is associated with cell proliferation and apoptosis, but its biological functions and role in glaucoma pathogenesis remain unclear. In the present study, we investigated the role of SNHG11 in TM cells using immortalized human TM and glaucomatous human TM (GTM 3 ) cells and an acute ocular hypertension mouse model. SNHG11 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…On the other hand, overexpression of XIAP and survivin can protect TM cells and ONH astrocytes from apoptosis induced by oxidative stress ( 208 ). Besides, a number of studies have identified that Rho/ROCK is involved in the pathogenesis of glaucoma ( 74 , 209 ). In patients with glaucoma, Rho/ROCK activation alters the cytoskeleton and increases TM cell adhesion, reducing aqueous humour outflow and increasing IOP ( 74 ).…”
Section: Regulators Of Apoptotic Pathway In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, overexpression of XIAP and survivin can protect TM cells and ONH astrocytes from apoptosis induced by oxidative stress ( 208 ). Besides, a number of studies have identified that Rho/ROCK is involved in the pathogenesis of glaucoma ( 74 , 209 ). In patients with glaucoma, Rho/ROCK activation alters the cytoskeleton and increases TM cell adhesion, reducing aqueous humour outflow and increasing IOP ( 74 ).…”
Section: Regulators Of Apoptotic Pathway In Glaucomamentioning
confidence: 99%
“…In patients with glaucoma, Rho/ROCK activation alters the cytoskeleton and increases TM cell adhesion, reducing aqueous humour outflow and increasing IOP ( 74 ). Additionally, Liu et al ( 209 ) reported that the long non-coding RNA small nucleolar RNA host gene 11 regulates Wnt/β-catenin signalling through Rho/ROCK via β-catenin phosphorylation at Ser675 or through GSK-3β-mediated phosphorylation at Ser33/37/Thr41, affecting TM cell proliferation, migration, apoptosis and autophagy. Therefore, the absence of activation of prosurvival genes in patients with glaucoma is a potential explanation for the increased vulnerability of the optic nerve to elevated IOP ( 210 ).…”
Section: Regulators Of Apoptotic Pathway In Glaucomamentioning
confidence: 99%